2019
DOI: 10.1002/glia.23569
|View full text |Cite
|
Sign up to set email alerts
|

A gene regulatory architecture that controls region‐independent dynamics of oligodendrocyte differentiation

Abstract: Oligodendrocytes (OLs) facilitate information processing in the vertebrate central nervous system via axonal ensheathment. The structure and dynamics of the regulatory network that mediates oligodendrogenesis are poorly understood. We employed bioinformatics and meta-analysis of highthroughput datasets to reconstruct a regulatory network underpinning OL differentiation. From this network, we identified families of feedforward loops comprising the transcription factors (TFs) Olig2, Sox10, and Tcf7l2 and their t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 73 publications
0
37
0
Order By: Relevance
“…Therefore, OLIG2 regulation might involve a delay mechanism to elongate the period and a mechanism to amplify dispersion. Recently, a similar method was used to analyze oligodendrocyte differentiation [52]. Similar to our study, the authors used a manual method to construct a network; however, they also introduced publicly available interaction data from omics databases.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Therefore, OLIG2 regulation might involve a delay mechanism to elongate the period and a mechanism to amplify dispersion. Recently, a similar method was used to analyze oligodendrocyte differentiation [52]. Similar to our study, the authors used a manual method to construct a network; however, they also introduced publicly available interaction data from omics databases.…”
Section: Discussionmentioning
confidence: 94%
“…In comparison with our method, this approach may reduce the number of false-negative interactions. On the other hand, the study [52] only focused on two-to four-node feedback loops. Our contraction method may detect a larger regulatory system of oligodendrocyte differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…So the exosomes secreted by MSCs have the effect of resistance to demyelination. Besides, myelination is a complex process which is regulated by micro RNAs, such as miR-219 and miR-338 (71,72). Milbreta et al applied a scaffolding system which enables sustained non-viral delivery of microRNAs to oligodendrocytes, and they found that the animals treated with miR-219/miR-338 preserved a higher number of Olig2, than the control group (73).…”
Section: Exosomes Are Expected To Be a Nano-therapeutic Agent For Depmentioning
confidence: 99%
“…Nowadays, concurrent integration of experimentally-derived omics data with a priori interaction data is a common approach in systems biology to obtain context-specific subnetworks 9 . To this end, a number of computational tools have been proposed by different groups to map and construct subnetworks from transcriptome data 10 and applied to several diseases, including breast cancer 11 , hepatocellular carcinoma 12, 13 , liver fibrosis 14 and neurodegenerative diseases 15 .…”
Section: Introductionmentioning
confidence: 99%